Network Analysis of the Relationship Between Trait Depression and Impulsiveness Among Youth - Zhang, Jingxuan; Li, Kuiliang; Xue, Yitong; Feng, Zhengzhi (Frontiers in Psychiatry, 2022)
Objective: Impulsiveness and trait depression are both the trait-level risk factors of depressive symptoms. However, the two traits overlap and do not affect depressive symptoms independently. This study takes impulsiveness and trait depression into a whole construct, aiming to find the complex associations among all facets and explore their relative importance in a trait network. It can help us find the key facets that need consideration in depression prevention. Methods: We used Barratt Impulsiveness Scale (BIS) and Trait Depression Scale (TDEP) as measuring tools, conducted network analysis, and applied Graphic Least Absolute Shrinkage and Selection Operator (GLASSO) algorithm to estimate the network structure and compute the linkage and centrality indexes. The accuracy and stability of the indexes were estimated through bootstrapping. All the computations were performed by R script and packages. Results: We found that “trait anhedonia” was connected with “non-planning” and “cognitive” impulsiveness, while “trait dysthymia” was connected with “motor” impulsiveness. “Cognitive” impulsiveness had statistically significant higher expected influence than “motor” impulsiveness and had the trend to be dominant in the network. “Trait dysthymia” had statistically significant higher bridge expected influence than “cognitive” impulsiveness and had the trend to be the key facet linking impulsiveness with trait depression. “Non-only children” had higher network global strength than “only children”. All indexes were accurate and stable. Conclusions: The present study confirms the complex associations among facets of trait depression and impulsiveness, finding that “cognitive” impulsiveness and “trait dysthymia” are the two key factors in the network. The results imply that different facets of impulsiveness should be considered respectively regarding to anhedonia and dysthymia. “Cognitive” impulsiveness and “trait dysthymia” are critical to prevention of depression.